Bile Acid Diarrhea in Adults and Adolescents. Issue 4 (9th November 2021) - Camilleri, Michael; Nurko, Samuel
ABSTRACT: Background: Bile acids are central to enterohepatic signaling pathways activated through natural receptors, farnesoid X receptor [FXR mediates synthesis of fibroblast growth factor‐19 (FGF‐19)], and G protein‐coupled bile acid receptor 1 (GPBAR1, also known as TGR5). Although bile acid diarrhea (BAD) is more commonly encountered in ileal resection or disease, there is evidence documenting "idiopathic" BAD in about 20% of adolescents and 30% of adults presenting with chronic, non‐bloody diarrhea often attributed to irritable bowel syndrome. Mechanism(s) leading to increased hepatic synthesis and colonic bile acid levels in "idiopathic" BAD include reduced synthesis of FGF‐19 by the ileal mucosa, or genetic variation in hepatocyte proteins klotho β and FGF receptor 4 (FGFR4) that mediate negative feedback of bile acid synthesis. Purpose: The objective of this review is to summarize the diagnosis of BAD in adults and adolescents. In addition to 75 SeHCAT retention for diagnosis of BAD, studies have validated fasting serum 7αC4 and FGF‐19, respectively, by‐product and inhibitor of hepatic bile acid synthesis, as well as fecal bile acid measurements. These assays are widely available through reference laboratories, and they are being simplified (eg, measurement of primary fecal bile acids in a random stool sample). BAD has also been identified as a co‐factor contributing to persistent diarrhea in other diseases in remission including inflammatory bowel disease, microscopic colitis, celiac disease, and neuroendocrine tumors. In summary, advances in diagnosis of BAD provide opportunities for generalists and pediatric and adult gastroenterologists to provide targeted treatment for BAD presenting as chronic non‐bloody diarrhea.